Testing The Moderator Role of Gender and Age in The Syrian Professional Accountants Acceptance Of Cloud Accounting Biased on The Unified Theory of Acceptance and Use of Technology (UTAUT). (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The purpose of this study is to test the moderator role of gender and age in Syrian professional accountants acceptance of cloud accounting, in the light of the extended unified theory of acceptance and use of technology (UTAUT2).Primary data were collected using a questionnaire developed biased on previous studies, and distributed to a sample of Syrian professional accountants. 106 acceptable responses were received. Data has been analyzed using two way AVOVA.The results showed that gender is moderating the relationship between effort expectancy and behavioral intention of Syrian professional accountants toward cloud accounting. Additionally, the results showed that age is moderating the relationship between each of (effort expectancy, hedonic motivation, price value) and behavioral intention (BI) of Syrian professional accountants toward Cloud Accounting.